Sistem Pemilihan Perumahan dengan Metode Kombinasi Fuzzy C-Means Clustering dan Simple Additive Weighting - Jaya, Tri Sandhika; Adi, Kusworo; Noranita, Beta (JSINBIS (Jurnal Sistem Informasi Bisnis), 2011)
Housing is one of human secondary needs. In selecting the most appropriate housing, there are lots of aspects to be considered to satisfy the costumers  want. In order to get optimal result, a system is needed to help the costumers to decide which housing fit them   most. System that will be built in this thesis is a system that supports costumers’ satisfaction in housing selection. There are 2 main stages in the  system,  namely  data  grouping  and  ranking.  Data  grouping  method  used  is  Fuzzy  C -Means  Clustering  (FCM).  Simple  Additive Weighting (SAW) is used for ranking purpose. Testing is carried out by comparing  interview result with system counting result. The testing result produces 9 cases that derive similar recommendation.Keywords : Housing selection; FCM; SAW; Recommendation; Grouping